HLA-DR(+) NK cells are mostly characterized by less mature phenotype and high functional activity - Erokhina, Sofya A (Immunol Cell Biol, 2017)
NK cells change their phenotype and functional characteristics during activation. In this work, we searched for a relationship of HLA-DR expression with differentiation stages and functional activity of NK cells ex vivo and stimulated in vitro with IL-2 challenged with gene modified feeder K562 cells expressing membrane-bound IL-21 (K562-mbIL21). This stimulation technique has been described for NK cell expansion in clinical use. We have observed that HLA-DR expression in freshly isolated circulating NK cells was mostly associated with less differentiated CD56(bright)CD57(−) cells, although in some individuals it could also be found in terminally differentiated CD57(+) cells. Ex vivo HLA-DR(+) NK cells possessed better capacity to produce IFN-γ in response to cytokine stimulation compared to their HLA-DR(−) counterparts. In vitro activation with IL-2 and K562-mbIL21 induces an increase in HLA-DR-positive NK cell proportion, again mostly among CD56(bright)CD57(−) NK cells. This happened in particular due to appearance of HLA-DR(+) expression de novo in HLA-DR-negative cells. Acquired in vitro HLA-DR expression was associated with NK cell proliferation activity, more intense cytokine-induced IFN-γ production, increased degranulation toward feeder cells, and higher expression of CD86 and NKG2D. Thus, stimulation with IL-2/K562-mbIL21 causes a significant phenotype and functional shift during NK cell activation and expansion.